Osteoradionecrosis of the mandible in patients with oropharyngeal carcinoma treated with intensity‐modulated radiotherapy. Issue 19 (13th June 2017) - Caparrotti, Francesca; Huang, Shao Hui; Lu, Lin; Bratman, Scott V.; Ringash, Jolie; Bayley, Andrew; Cho, John; Giuliani, Meredith; Kim, John; Waldron, John; Hansen, Aaron; Tong, Li; et al.
Abstract : BACKGROUND: Osteoradionecrosis (ORN) of the mandible is a late toxicity affecting patients treated with radiotherapy for head and neck malignancies. To the authors' knowledge, ORN has no standardized grading system and its reporting is based on retrospective findings in heterogeneous patient populations. The rate of ORN in the era of intensity‐modulated radiotherapy (IMRT) still is unknown. METHODS: The authors report the incidence of ORN from prospectively collected data regarding 1196 patients who were diagnosed with squamous cell carcinoma of the oropharynx and treated with curative‐intent IMRT, with or without concomitant systemic treatment, from January 2005 to December 2014. Each case of ORN was graded according to its severity. Clinical and dosimetric comparisons were performed between patients with ORN and a matched control cohort of patients without ORN. RESULTS: The actuarial rate of ORN of the mandible was 3% at 1 year, 5% at 3 years, and 7% at 5 years. On multivariable analysis, smoking (hazard ratio, 1.9; 95% confidence interval, 1.07‐3.4 [ P  = .03]) and T classification (hazard ratio, 1.78; 95% confidence interval, 1.02‐3.1 [ P  = .041]) were found to be statistically significant risk factors. The presence of cardiovascular comorbidities, use of bisphosphonates, and pre‐IMRT dental extractions were found to be different between the matched cohorts. The mandibular volume receiving 50 grays (Gy) (in cm 3 ) and the volume receiving 60 Gy (in cm 3 ) were found to be associated with ORN on multivariable analysis in the matched cohort patients receiving an IMRT regimen of 2 Gy per fraction. CONCLUSIONS: ORN is relatively uncommon among patients with oropharyngeal carcinoma who are treated with IMRT, but continues to occur beyond 5 years after treatment. Modifiable risk factors that are associated with higher rates of ORN include smoking and the use of bisphosphonates. Minimizing the volumes of the mandible receiving >50 Gy or > 60 Gy also may have an effect on the ORN rate. Cancer 2017;123:3691–3700. © 2017 American Cancer Society Abstract : In the current study, the authors report the actuarial rates of mandibular osteoradionecrosis in patients treated at the study institution with organ‐sparing intensity‐modulated radiotherapy for squamous cell carcinoma of the oropharynx. They analyze which clinical, dental, and intensity‐modulated radiotherapy dose/volume variables may be associated with the development of osteoradionecrosis.